Empirical validation of the integrative psychological group intervention for women with breast cancer – preliminary results - Novakov, Ivana; Popovic-Petrovic, Svetlana; Dugandžija, Tihomir; Tatić, Milanka (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Breast cancer diagnosis is an extremely stressful life event that brings a number of physical and psychological challenges. However, supportive and psycho-educational group interventions can significantly decrease psychological distress in patients. The aim of this study was to empirically validate the effects of the integrative psychological group intervention, regarding the affective state of women who underwent breast cancer surgery at the Oncology Institute of Vojvodina. Methods. This study was conducted on a sample of 30 women, with the average age of 53.17 years (standard deviation – SD = 10.09). Following the surgical intervention, the inpatients participated in an integrative group session consisting of the following parts: 1) supportive-expressive, 2) psycho-educational and 3) health-educational. Before the session, participants filled in a demographic data questionnaire, measures of positive and negative affect (PANAS), optimism (LOT-R), hope (AHS), neuroticism (BFI) and symptoms of depression (DASS-21). At the end of the group sessions, the participants filled in the PANAS again. Results. A paired-samples t-test showed that following an intervention, a statistically significant increase in positive affect had occurred (t(29) = -4.44, p < 0.001). For negative affect, the t-test also yields the statistically significant results (t(29) = 5.60, p < 0.001), showing that intervention led to a significant decrease in negative affect. The nonparametric Wilcoxon Signed-Rank test also confirmed these results. The multiple regression analysis (F (4, 25) = 3.46, p = 0.02) showed that high neuroticism and low symptoms of depression significantly predicted a greater increase in positive affect following the session. Another regression analysis (F (4, 25) = 3.32, p = 0.03) showed that the higher symptoms of depression and, marginally, higher hope significantly predicted a greater decrease in negative affect. Conclusion. Our results showed that the integrative psychological group intervention had positive short-term effects regarding the affective state of women who underwent breast cancer surgery, and that different psychological variables can play a significant role in prediction of changes in patients’ affect.
Keywords: breast neoplasms; postoperative period; integrative oncology; psychotherapy group; surveys and questionnaires; women; treatment outcome